The Influence of Southern USA Writers on Horst Bienek's Gleiwitz Tetralogy - McIvor, Joseph Gerard (Trinity College Dublin. School of Lang, Lit. & Cultural Studies. Discipline of German, 2025)
This thesis examines the influence of four Southern USA writers (William Faulkner, Thomas Wolfe, Carson McCullers, and Truman Capote) on Horst Bienek's portrayal of Upper Silesia's final years as a German province in the four novels of the Gleiwitz tetralogy: Die erste Polka (1975), Septemberlicht (1977), Zeit ohne Glocken (1979), and Erde und Feuer (1982). The tetralogy is Bienek's epic literary memorial to his now disappeared childhood province (in 1945 Upper Silesia became sovereign Polish territory). The author was born in the industrial border city of Gleiwitz in German Upper Silesia in 1930, and died in Munich in 1990. Chapter 1 begins with introductory remarks, and a review of current research on Horst Bienek's literary work. This is followed by short analysis of the reception of US literature in post-war Germany. The main body of the chapter explains and contextualises data relating to the two regions, Upper Silesia and the American South, with which this study is concerned. This includes historical analyses of critical periods in both regions, and a review of Bienek's short story Wallfahrt zu Sankt Anna (1968). Topics such as liminality, myth, and Bienek's use of the Southern grotesque genre are also discussed. The chapter concludes with a short analysis of intertextuality and appropriation (Bienek was a prolific user of intertexts in the Gleiwitz tetralogy). Chapter 2 is devoted to an analysis of poetischer Realismus, the narrative style Bienek adopted in the tetralogy, which he believed derived from the four Southern writers. The chapter examines in depth attributes of Horst Bienek's poetic realist style, and its relationship to that of the nineteenth-century German poetic realist epoch. The three succeeding chapters are dedicated to the four Southern authors themselves (McCullers and Capote are discussed in a joint chapter). Each chapter in its own way elucidates how the Southerners fictional reconstruction of disappearing, liminal and cursed Southern spaces shaped and defined how Bienek would memorialise his own lost German borderland province. Chapter 3 (William Faulkner, 1897-1962) focuses on significant Faulkner tropes such as identity, history, the myth of the South, the significance of the past, and Faulkner's literary style, all of which were compelling for Bienek as he engaged with his Gleiwitz memorial. A significant section of the discourse examines the divided identity issues of several Bienek and Faulkner protagonists. The emphasis in Chapter 4 (Thomas Wolfe, 1900-1938) is on one Wolfe novel, Look Homeward, Angel, to which Horst Bienek had a strong emotional attachment, and which exerted considerable influence on the author's Gleiwitz writing. The chapter investigates Wolfe's aesthetics and how these impacted upon Bienek's tetralogy, and discusses Bienek's poetic realist approach to the use of history and memory in the tetralogy. Finally, the themes of loneliness, longing and the loss of homeland are discussed. The focus in Chapter 5 (Carson McCullers, 1917-1967, and Truman Capote, 1924-1984) is again on aspects of Bienek's understanding of poetic realism, on rite-of-passage as an analogue for a liminal province, and on Bienek's development of a Southern grotesque aesthetic for Upper Silesia. Four novels by McCullers, and a single work by Truman Capote (Other Voices, Other Rooms) are discussed, all of which impacted significantly on Bienek's Gleiwitz novels. All three chapters dealing with the individual Southern writers include analyses of Bienek's intertextual use in the tetralogy of appropriated texts, where the author replicates situations, plotlines, motifs, and character attributes from each of the Southern writers. These sections demonstrate that the appropriated texts have, in the context of the Upper Silesian tetralogy, been effectively transformed into something new, creative, instructive, and meaningful.
APPROVED
Keywords: Horst Bienek; William Faulkner; Thomas Wolfe; Carson McCullers; Truman Capote; Upper Silesia; Gleiwitz Tetralogy; Poetic Realism; Intertextuality; Liminality; Die erste Polka; Septemberlicht; Zeit ohne Glocken; Erde und Feuer; Other Voices Other Rooms; The Member of The Wedding; The Heart is a Lonely Hunter; As I Lay Dying; The Sound and the Fury; Look Homeward Angel; The US Southern States; Poetischer Realismus; Symbolic Realism; Light in August; Absalom Absalom!